Addressing prevention and management of wasting and nutritional oedema in children requires an improved evidence base on resource use and cost-effectiveness of interventions - Huybregts, Lieven; Berkley, James A.; Castro, Mary Christine; Dewey, Kathryn G.; Golden, Kate; Jemutai, Julie; Naude, Celeste E.; McCaul, Michael; Daniel, Allison I. (BMJ, 2025)
Effectiveness studies on the prevention and management of wasting and nutritional oedema should ideally include the evaluation of resource use and cost-effectiveness (CE) to allow future guideline development to appreciate this dimension. Research focusing on resource use and CE should comply with health economic evaluation reporting standards. Reports should aim to present data on resource use and CE disaggregated by cost input and present data using different costing perspectives, such as provider and beneficiary. This enhances cross-study comparability and increases their relevance for guideline development. The inclusion of standardised health outcomes, such as disability-adjusted life years, which allow policymakers in resource-limited settings to compare a wide range of available interventions, is useful.